(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
The use of medicinal plants as a core component of the traditional African health care system is perhaps the oldest and most diverse of all therapeutic approaches. Traditional herbal healers are, in many parts of rural Africa, the most readily accessible and affordable health resource available to the local population and, at times, the only surviving treatment. Finding a suitable solvent is important to obtain a high yield of antioxidants in the phytochemicals present in C. africana. Among the solvents, methanol displayed the highest capacity in extracting glycosides (223.12±1.20 mg LE/g dry weight) phenolics (89.09±0.24 (mg GAE/g dry weight) and flavonoids (80.88±0.24 mg QE/g dry weight) from C. africana stem bark extract. Closely related trend was observed in glycosides, phenolics and flavonoids extracted with n-hexane. These findings suggest a high number of polar glycosides and phenolics in the stem extract of C. africana. These findings validate the pharmacological activities of the plant in Africa.